Cyberbullying And Cyberstalking: Their Influence on The Social and Emotional Development of Teenagers in India - Rachna; Dr. Rahul Varshney (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The advent of the internet and digital communication has revolutionized the way teenagers interact, learn, and express themselves. However, along with the benefits of technology, there come significant challenges, particularly in the form of cyberbullying and cyberstalking. These online threats have a profound influence on the social and emotional development of teenagers in India, affecting their well-being, relationships, and overall growth. This comprehensive article explores the prevalence, types, and consequences of cyberbullying and cyberstalking in the Indian context. Drawing from existing research, case studies, and interviews, it highlights the need for effective preventive measures and intervention strategies to protect adolescents' mental health and development in the digital age. Sometimes, in today's modern society, we lose touch with our roots because we're too focused on showing off. We also don't always know how someone will react, especially when they spend a lot of time online. In India, there aren't any specific laws that directly address cyberbullying and cyberstalking, leaving victims without proper protection.